2019
DOI: 10.4309/jgi.2019.43.5
|View full text |Cite
|
Sign up to set email alerts
|

Does Sports Betting Affect Investment Behaviour? Evidence from Ghanaian Sports Betting Participants

Abstract: The study sought to assess the impact of sports betting on the investment behaviour of Ghanaians, focusing on sports betting centers within the Accra Metropolis, Ghana. The objectives of this observational study were to determine how individuals perceive the risk of sports lotteries as opposed to investment, to determine if sports lottery was viewed as an alternative to investments and savings, and to understand how participation in sports lotteries affects individuals’ ability to save and invest. In adopting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…In recent times sports betting has become a serious problem, [14]- [17] which calls for research and understanding. Koross [18] indicates that the youth have resorted to betting and at times do so at the expense of their studies.…”
Section: A Statement Of the Problemmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent times sports betting has become a serious problem, [14]- [17] which calls for research and understanding. Koross [18] indicates that the youth have resorted to betting and at times do so at the expense of their studies.…”
Section: A Statement Of the Problemmentioning
confidence: 99%
“…It is worrying because instead of the students using their precious time to work on their projects, assignments, and have some rest to enable them to regain enough strength for the following week, they resort to sports betting. Some studies on sports betting by Latvala, Castr´en, Alho and Salonen [20], and Ofosu and Kotey [17], revealed that students who engage in sports betting experience work and educational disruption.…”
Section: A Statement Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…The study discovered that habitual betting among Christian youth were caused majorly by unemployment, peer pressure, early exposure to betting games, advertisements and desire to escape from reality. Ofosu and Kotey's (2020) research investigated sports betting and investment behaviour among Ghanaians with the intention of establishing betting as investments to bettors. The study revealed that participants saw it as an opportunity to improve their finances, but did not see it as substitute for investments.…”
Section: Betting Games/gambling In Africamentioning
confidence: 99%